Práticas de escrita do gênero relato de experiência: proposições didáticas para a EJA - Leite , Glória Maria dos Santos (2021)
The difficulties faced by students of Youth and Adult Education - EJA, with regard to written production, have revealed the need for the teacher to emphasize the teachinglearning of writing as a social practice, taking into account the different contexts in which these subjects are inserted, their experiences, needs and desires. Another aggravating factor concerns the fact that writing is still worked as a product, even in the face of all the theoretical perspectives that understand it as a process, consisting of stages such as elaboration, review and rewriting. Such findings motivated us: (1) to discuss the notion of written production, according to the socio-interactionist perspective, which will support the approach to the Experience Report genre and the construction of the proposed activities with this genre for EJA students; (2) the proposition of didactic activities that allow the written production of this genre, in order to encourage students to reflect on their own history and also the social function and the elements that constitute it; and, finally, (3) the elaboration of a Pedagogical Notebook consisting of activities, which can be implemented in the daily life of EJA. In view of these issues, we have outlined as a general objective: to foster writing practices with thetextual genre Experience Report, based on the proposition of a set of didactic strategies with the aforementioned gender.As a theoretical contribution, we are guided by Paulo Freire (1987, 1996, 2003) and Gadotti (2011), to discuss Youth and Adult Education. On teaching Portuguese and writing, we started with Koch and Elias (2018), Geraldi (1997), Antunes (2003, 2005, 2009), Passarelli (2004, 2012), Ferrarezi Jr. and Carvalho (2015). To talk about textual genres, we used Bakhtin (2011), Marcuschi (2002, 2008), Geraldi (1997, 2005), Koch (2011), Antunes (2003, 2005), Ferrarezi and Carvalho (2015). Regarding the report genre, we started from the studies of Signorini (2006) and Faraco (2010), among others. In addition to these and other references, we seek, throughout this work, to use the National Common Curricular Base - BNCC (2017) and the National Curriculum Parameters - PCN (1998), in order to highlight the skills and abilities in written production to be achieved by the students. This is a research with a qualitative approach in which the case study was adopted as a method; it also has a propositional character, as already announced in the research objective. As a result, we present a Pedagogical Notebook, which has the function of serving as a didactic instrument in the classroom for the researcher teacher, as well as for other teachers who, perhaps, may use it as suggested or with adaptations. In it, there is a compilation of didactic activities aimed at the written production of the genre Relato de Experience, a textual genre designed to motivate students to expand their skills in reading and writing, through an exercise of expressing their own life experiences. We present a Pedagogical Notebook, which has the function of serving as a didactic instrument in the classroom for the researcher teacher, as well as for other teachers who, perhaps, can make use of it as suggested or with adaptations. In it, there is a compilation of didactic activities aimed at the written production of the genre Relato de Experience, a textual genre designed to motivate students to expand their skills in reading and writing, through an exercise of expressing their own life experiences.